2017
DOI: 10.1085/jgp.201611677
|View full text |Cite
|
Sign up to set email alerts
|

The HOOK region of voltage-gated Ca2+ channel β subunits senses and transmits PIP2 signals to the gate

Abstract: Voltage-gated Ca2+ channels contain β subunits that regulate channel gating. Park et al. conduct a comprehensive analysis of the role of the β subunit HOOK region and show that its B domain is important for PIP2 regulation of channel gating and that its A domain modulates this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…We recently found that 2 hydrophobic Phe residues in the B domain are needed for decreasing the inactivation kinetics and PIP 2 sensitivity of the Ca V 2.2 channels. 24 Consistently, the Phe-mutated form (b2cPhe Ala ) also slightly decrease the current density of the channels (Fig. 3C and D).…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…We recently found that 2 hydrophobic Phe residues in the B domain are needed for decreasing the inactivation kinetics and PIP 2 sensitivity of the Ca V 2.2 channels. 24 Consistently, the Phe-mutated form (b2cPhe Ala ) also slightly decrease the current density of the channels (Fig. 3C and D).…”
Section: Resultssupporting
confidence: 73%
“…24 Here, we examined whether the HOOK region of the b subunit also affects the voltage-dependent inactivation (VDI) and voltage-dependent activation (VDA) of the Ca V channels. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations